1962
DOI: 10.2307/4591708
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Kolmer Reiter Protein and Fluorescent Treponemal Antibody Tests

Abstract: reproducibility. This usage is particularly true

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

1964
1964
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
1
1
0
1
Order By: Relevance
“…The result of this comparison showed that the FTA test possessed a specificity and sensitivity exceeding that of the other treponemal tests and equal to that of the nontreponemal tests which were in routine use (68). Several evaluations (2,5,13,27,37,40,52,53,56,62,70,71,76,82,91) have confirmed the earlier work of Deacon and his associates and have, in general, validated the specificity and sensitivity of the FTA test with sera from a variety of patients under a variety of test conditions. The procedure for performance of the FTA-200 test was included in "Serologic Tests for Syphilis" in 1964 (82a), and protocols for testing of the reagents employed in this test were published (73).…”
Section: Detection Of Treponerma Pallidum and Its Antibodysupporting
confidence: 60%
“…The result of this comparison showed that the FTA test possessed a specificity and sensitivity exceeding that of the other treponemal tests and equal to that of the nontreponemal tests which were in routine use (68). Several evaluations (2,5,13,27,37,40,52,53,56,62,70,71,76,82,91) have confirmed the earlier work of Deacon and his associates and have, in general, validated the specificity and sensitivity of the FTA test with sera from a variety of patients under a variety of test conditions. The procedure for performance of the FTA-200 test was included in "Serologic Tests for Syphilis" in 1964 (82a), and protocols for testing of the reagents employed in this test were published (73).…”
Section: Detection Of Treponerma Pallidum and Its Antibodysupporting
confidence: 60%
“…The fluorescent antibody technique has been used in studying or identifying nonspecific thyroiditis (819), human submaxillary gland mucin (243), human and simian malaria (274), mouse mammary tumor agent (81), various malignant human tumors (95), renal lesions in systemic lupus erythematosus (88), disappearance of a liver-specific antigen in hepatomas (160), hog cholera virus (463), equine encephalomyelitis virus (324), poliomyelitis antibodies by an indirect method (399), pleuropneumonia-like organisms in human tissues (101), single cells of Shigella flexneric (115), trachoma, psittacosis, and lymphogranuloma venereum (350), enteropathogenic E. coli in infant stools (308), various mycobacteria and corynebacteria (535), treponemal diagnostic tests (495), and localization of specific antigens in Paramecium aurelia (38).…”
Section: Drugsmentioning
confidence: 99%
“…Por esto, las pruebas serológicas de la sífilis tienen tanta importancia en el di;:ignóstico clínico de la enfermedad. Existen revisiones y clasificaciones de las pruebas existentes 4, 9, 12 • rn, 22 • 23 • Elkerton 5 aconseja llevar a cabo un plan s.erológico de diagnóstico con una prueba cardiolipídica y dos treponémicas. En España habitualmente Vol.…”
Section: Introductionunclassified